Elaboration Model for Sustainable Development Education in CSR and Community Development Courses - Yani Hendrayani (Cita Konsultindo Research Center, 2023)
As stated in SDGs 4.7, education for sustainable development functions to educate the younger generation as future leaders and agents of change. This research aims to identify student motivation towards CSR and Community Development lecture messages on sustainable development issues. Communication plays a role in the process of achieving lecture goals. This research uses the Elaboration Likelihood Model theory to determine changes in student attitudes regarding the message of sustainable development education. The research uses a quantitative approach by observing through surveys and using non-probability sampling, namely judgment sampling on active students in CSR and Community Development courses at UPN Veteran Jakarta, namely 241 students. Determining the sample size used the Cochran formula and obtained 51 respondents. The results of this research using the Elaboration Likelihood Model theory show that lecture messages have not significantly influenced student attitudes. Following the research results, to strengthen students' motivation and abilities, they can use exciting communication strategies that generate emotional liking for lecture messages about sustainable development issues in CSR and Community Development courses. Lecturers must also carry out Project Learning methods so that students are immersed in the field to awaken the emotional side of students regarding sustainable development issues.